PENGARUH TERAPI BERMAIN EDUKATIF FLASHCARD TERHADAP KECEMASAN PRE ANESTESI UMUM PASIEN ANAK USIASEKOLAH DI RUMAH SAKIT PKU MUHAMMADIYAH YOGYAKARTA - Setyowati, Riana Rahmania; Handayani , Nia (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Background: High anxiety in pediatric patients, if not promptly addressed, can lead to the postponement or cancellation of surgical procedures. This preoperative anxiety is closely related to the quality of education provided beforehand. To better prepare pediatric patients for surgery, educational play therapy with flashcards is recognized as an effective method. Objective: This study aimed to investigate the effect of educational flashcards play therapy on pre-anesthesia anxiety in school-aged pediatric patients at PKU Muhammadiyah Hospital, Yogyakarta. Method: This study employed quantitative research method with pre-experimental design using a one group pretest-posttest design without a control group. Sampling was conducted via accidental sampling, with a total of 25 respondents. Result: The Wilcoxon signed-rank test yielded a p-value of 0.000. This p-value indicates that it is less than α (0.05), which suggests a highly significant effect in this study. Conclusions: There is a significant effect of educational flashcards play therapy on pre-anesthesia anxiety in school-aged pediatric patients. Recommendations: Further research could explore more innovative educational play therapy media tailored to children's developmental stages to expand options for play therapy aimed at alleviating preoperative anxiety in children.